Black wind - Cussler, Clive (Cussler, Clive. Dirk Pitt adventure., 2004)
In the waning days of World War II, the Japanese tried a last desperate measure-a different kind of kamikaze mission, this one carried out by two submarines bound for the West Coast of the United States, their cargo a revolutionary new strain of biological virus. Neither sub made it to the designated target. But that does not mean they were lost. Someone knows about the subs and what they bore, knows too where they might be, and has an extraordinary plan in store for the prize inside-a scheme that could reshape the world as we know it. All that stands in the way are three people: a marine biologist named Summer, a marine engineer named Dirk, and their father, Dirk Pitt, the new head of NUMA. Pitt has faced devastating enemies before, and has even teamed up with his children to track them down. But never has he looked upon the face of pure evil . . . until now.